Lebak Larang: Analisis Toponimi - Ahmad Feisal Riza (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
The study of place names is very interesting to research. This happens because the names of these places have different origins. The study of place names can add to our cultural and social insight. Giving place names in some areas of Cibeunying Landeuh cannot be separated from the stories that develop in the community. The method used in this research is descriptive qualitative with place names as data. This study will describe the origin of place names in Cibeunying Landeuh.